O-070 Double stimulation in egg donors: is an adequate strategy to optimize the gamete donation program?. (30th June 2022) - Cruz Palomino, M; Henzenn, E; Vergara, V; Requena, A
Abstract: Study question: Is double stimulation (DuoStim) a viable strategy to optimize the performance of the egg donation program? Summary answer: Carrying out two consecutive stimulations in the gamete donation program allows the number of donations to be increased, optimizing its efficiency while maintaining donor safety. What is known already: DouStim (double stimulation) consists of two successive ovarian stimulations in the follicular and ensuing luteal phase with two oocyte retrievals at the end of both ovarian stimulations. This non-conventional strategy, developed to retrieve the greatest number of oocytes in the shortest possible time, was designed initially to optimize clinical outcomes in poor ovarian response, but double stimulation could be useful in patients with a good prognosis such as oocyte donors to optimize the program efficacy. Study design, size, duration: Prospective and observational analysis performed in IVI Madrid between September and December 2019. Participants underwent the same stimulation protocol in the follicular phase and for luteal phase stimulation. The study was approved by an Institutional Review Board (1903-MADR-034-AR) and all women provided written informed consent. Participants/materials, setting, methods: Follicular and luteal-phase stimulation was the same for all the donors; daily tablet of 10 mg of acetate of medroxyprogesterone (AMP) from first day of stimulation, 225 IU/day recombinant FSH and triggering with 0.1 mg GnRH agonist. To analyze the differences in clinical results between both phases of the cycle, independent donations were made after each oocyte retrieval. Statistical analyses were performed using the Statistical Package for Social Sciences 19.0 (IBM Corporation, Armonk, NY, USA). Main results and the role of chance: We included 60 egg donors for a total of 88 recipients who received oocytes retrieved in both the follicular and luteal phases. Although the number of oocytes and metaphase II was significantly higher in the follicular phase compared to the luteal one, 19.8 ± 2.0 vs. 13.3 ± 2.2 oocytes, p < 0.001 and 16.4 ± 1.8 vs. 11.5 ± 2.1 MII, p < 0.001, then this disparity in the results disappears since the rate of usable blastocyst is similar with the same proportion of frozen embryos in both stimulation phases (4.0 ± 0.6 vs. 4.4 ± 0.8, p = 0.451). According to the clinical results, we did not observe significant differences between the follicular and the luteal phase neither for the implantation rate (69.8% vs. 66.1%, p = 0.783), nor for the clinical pregnancy rate (71.2% vs. 66.7%), confirming the possibility of being able to make independent donations of each of the stimulated phases without affecting the chances of success. Limitations, reasons for caution: This is an observational study and thus possible confounders cannot be completely excluded. More data are needed to draw firm conclusions and it will be critical to increase the sample size to check if the results observed in this work remains in the general population Wider implications of the findings: As far as we know, this is the first study in which a double stimulation protocol is applied in oocyte donors. The fact of being able to increase the number of donations in the same stimulation cycle allows us to improve the efficiency of the egg donation program. Trial registration number: Not apply